THE CONCEPT OF TARETAN DHIBI’ IN THE FRAME OF MADURESE RELIGIOUS MODERATION - Nor Hasan; Nurul Qomariyah (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2023)
Taretan dhibi' is one of the cultural enculturations of the Madurese people. This study attempts to investigate the Madurese people's cultural concept of the taretan dhibi’. The term taretan for Madurese people is the concept of relatives with the ideology of Madurese people who have a cultural obligation to maintain emotional interactions and kinship ties between one another. It is quite fascinating to study the concept of religious moderation due to the social style of Madurese society itself which is different from other regions. therefore, despite all of their distinctions in terms of religion, customs, and traditions, the author will look at how the Madurese people carry out the concept of taretan dhibi. Through descriptive phenomenological analysis, this research reveals that taretan dhibi' is a manifestation of the emotional ties between Madurese people. Thus, the form of religious moderation in the cultural concept of taretan dhibi' is firstly respecting brothers and sisters (mentioned in Madura as taretan) by allowig any kind of differences and providing space for self-expression. The concept of